If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) = x + (x + 2) + (3x + -1) Reorder the terms: 3(2 + x) = x + (x + 2) + (3x + -1) (2 * 3 + x * 3) = x + (x + 2) + (3x + -1) (6 + 3x) = x + (x + 2) + (3x + -1) Reorder the terms: 6 + 3x = x + (2 + x) + (3x + -1) Remove parenthesis around (2 + x) 6 + 3x = x + 2 + x + (3x + -1) Reorder the terms: 6 + 3x = x + 2 + x + (-1 + 3x) Remove parenthesis around (-1 + 3x) 6 + 3x = x + 2 + x + -1 + 3x Reorder the terms: 6 + 3x = 2 + -1 + x + x + 3x Combine like terms: 2 + -1 = 1 6 + 3x = 1 + x + x + 3x Combine like terms: x + x = 2x 6 + 3x = 1 + 2x + 3x Combine like terms: 2x + 3x = 5x 6 + 3x = 1 + 5x Solving 6 + 3x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 3x + -5x = 1 + 5x + -5x Combine like terms: 3x + -5x = -2x 6 + -2x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + -2x = 1 + 0 6 + -2x = 1 Add '-6' to each side of the equation. 6 + -6 + -2x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 1 + -6 -2x = 1 + -6 Combine like terms: 1 + -6 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5
| X+X=(30*3*2) | | -6-3(2k+4)=-8 | | 4(2x-3)=-5 | | 3x(2x-3)=0 | | 6x^2+4x-54=0 | | 4x+6x=10x | | p+p+p+p= | | 19=3x | | X(4X+5)-3=0 | | X(4X+5)-3=5 | | 4(-4t^2+27-45)=0 | | 5x-3=-1 | | 9x^2+60x+100=0 | | 6(3-a)+7(3a+2)-4(a+5)= | | 9x-5x+8x-6x= | | (2+y)+y=4 | | 15-13x-20x^2=0 | | -X+2y=1 | | 5+(2-3)-(6-4)+7= | | 2x-10=48 | | 14+(-3)-(-6)+8= | | 7(2)+7y=-10 | | 72+7y=-10 | | X+(2+X)=4 | | 54+68=158 | | 6(k-2)-7=3k-(2k-3) | | 6w^2-4w^3= | | 1/2(6x+4)=x+2(x+1) | | 2(x+1)=8-x | | 4a-5=2(a+1)+9a+2 | | x-6=2(x-5)-6(x-4) | | 21.00+0.50x-0.50x=1.50x-0.50x |